Noken, Women's Identity Space and Strategy In Power Contestation - Godefridus Samderubun; Heru Nugroho; Suharko Suharko (Pelopor Publikasi Akademika, 2023)
Asmat women have undergone a process of transformation due to contact with the agents present and changing the pattern of existing gender relations. This intersection has given birth to a new process of creation regarding women's space and identity. This paper will discuss the impact of the transformation of gender relations experienced by Asmat Women. The impact that occurs then needs to be seen in relation to the current context of the new conditions that occur in it, especially in the space of women's cultural identity which is now embedded and as if produced as a cultural identity for Asmat women, namely noken. Bourdieu's perspective is used to look at agents who fall into the scale of gender relations transformation, namely investors, traders, buyers and the many economic spaces that are also present in it. Noken as part of the results of the process of gender relations transformation occurred in Papua, especially in Asmat. The research method used is qualitative method of analysis The results of the study show that Asmat Tribe Women find themselves in the process of identity reconstruction that they begin to interpret with actions and efforts on the awareness they have. The transformation process that occurs due to the intervention of agents is seen as part of a change that they cannot control but can manage for the benefit they are trying to achieve as